Assesment of Innovation Process Capability-Based on Innovation Value Chain Model in East Java Footwear Industry - Lianto, Benny; Wahyudi, Rahman Dwi; Rinawiyanti, Esti Dwi; Herninda, Aziera (School of Business and Management Institut Teknologi Bandung, 2015)
Abstract. This study attempts to assess the innovation process based on innovation value chain model in footwear industry in East Java, Indonesia. A strength and weakness mapping analysis was performed and it included three factors related to company characteristics: operation scale based on number of employees, operational priod, and market orientation. The samples were 62 footwear industries, members of East Java Indonesian Footwear Association (Aprisindo). The questionnaire was sent via email. Thirty industries (48.38%) sent the questionnaire back. A focus group discussion (FGD) was conducted with several representatives from footwear industry before the questionnaire was sent. The study found that companies are relatively good at idea conversion (42,30%) but the companies have a little difficulties at diffusion (50,80%) and at idea generation (55,80%). From the result respose show (see table.2) that the weakest links (the innovation process bottleneck) is cross-pollination activity [in which the people typically don't collaborate on projects across units, businesses, or subsidiaries (88,6%)], while the strongest links is selection activity [the companies have a risk- averse attitude toward investing in novel ideas (39,3%)]. Based on p-value, the study found that company characteristics influencing a certain phase of innovation value chain significantly were company period (age of company) and market orientation. Specifically, both of them influenced idea generation phase.Keywords: Innovation Process Capability, Innovation value chain, footwear industry.